Lagrangian evolution of DMS during the Southern Ocean gas exchange experiment: The effects of vertical mixing and biological community shift. Issue 12 (11th December 2013) - Yang, M.; Archer, S. D.; Blomquist, B. W.; Ho, D. T.; Lance, V. P.; Torres, R. J.
Abstract : [1] Concentrations of dimethylsulfide (DMS) and its precursor dimethylsulfoniopropionate (DMSP) are highly variable in time and space. What is driving the variability in DMS(P), and can those variability be explained by physical processes and changes in the biological community? During the Southern Ocean Gas Exchange Experiment (SO GasEx) in the austral fall of 2008, two 3 He/SF6 labeled patches were created in the surface water. SF6 and DMS were surveyed continuously in a Lagrangian framework, while direct measurements of air‐sea exchange further constrained the gas budgets. Turbulent diffusivity at the base of the mixed layer was estimated from SF6 profiles and used to calculate the vertical fluxes of DMS and nutrients. Increasing mixed layer nutrient concentrations due to mixing were associated with a shift in the phytoplankton community structure, which in turned likely affected the sulfur dynamics on timescales of days. DMS concentration as well as air‐sea DMS flux appeared to be decoupled from the DMSP concentration, possibly due to grazing and bacterial DMS production. Contrary to expectations, in an environment with high winds and modest productivity, physical processes (air‐sea exchange, photochemistry, vertical mixing) only accounted for a small fraction of DMS loss from the surface water. Among the DMS sinks, inferred biological consumption most likely dominated during SO GasEx. Key Points: DMS concentration demonstrated large variability in a Lagrangian framework Vertical mixing diluted surface DMS stock but increased nutrient availability DMS production (DMSP) modeled from bulk does not capture rapid changes